Pengaturan Euthansia Ditinjau dari Hukum Pidana dan Hukum Kesehatan Perspektif Hak Asasi Manusia - Wahyudi, Pipin; Yunaldi, Wendra (Universitas Pahlawan Tuanku Tambusai, 2024)
Euthanasia is a very controversial issue in Indonesia, with many pro-contracts linked to the issue of euthanasy. For the implementation of euthanasia is not permitted to be carried out in Indonesia, which is in violation of the provisions of article 344 of the Covenant and article 461 of the Act No. 1 of 2023. Besides, euthanasia is prohibited because it violates the code of medical ethics. And human rights also prohibit euthanasia on grounds contrary to a person's right to life. Countries that legalize euthanasia are Switzerland, the Netherlands, Belgium, Luxsembor, Colombia, Canada, Austria, Spain, and Victoria. The state legalizes euthanasia on different grounds between suicide and voluntary death, and the state grants the patient the right to autonomy. This study uses normative legal research methods using skunder data consisting of primary, secondary, and tertiary legal material as well as approaches used by studying the legal norms and regulations of the law related to euthanasia. The legal material that has been collected is then compiled regularly and systematically then analyzed using methods of skinative analysis. The problems that this study seeks to solve are how euthanasia is regulated in States that legalize euthenia and how it is reviewed from health law and human rights criminal law.